The North Negros Forest Reserve : A Biodiversity Hotspot at Risk - Hamann, Andreas (Silliman Journal, 2022)
This report outlines the results of habitat surveys, ecological research, species inventories, and conservation efforts that have been conducted in the North Negros Forest Reserve (NNFR) in Negros Occidental between 1995 and 2000 by a team of scientists and environmental workers. The habitat survey revealed that 50 years after its establishment the reserve still holds 4,700 ha of mid-elevation oldgrowth forest, 5,200 ha of high-elevation mossy forest, and 6,600 ha of secondary forest. Mainly due to its elevational gradient, the NNFR contains a stunning diversity of habitats despite its small size. Interviews and site inspections at 20 villages in the reserve pointed towards some of the immediate threats to the reserve and its wildlife such as small-scale logging, forest extraction, and hunting. Important first steps to constructively manage and protect the reserve are discussed in this paper.